CMV Status Drives Distinct Trajectories of CD4+ T Cell Differentiation - Zhang, Weiwen; Morris, Anna B.; Peek, Erica V.; Karadkhele, Geeta; Robertson, Jennifer M.; Kissick, Haydn T.; Larsen, Christian P. (Frontiers in Immunology, 2021)
Cytomegalovirus (CMV) is one of the most commonly recognized opportunistic pathogens and remains the most influential known parameter in shaping an individual’s immune system. As such, T cells induced by CMV infection could have a long-term impact on subsequent immune responses. Accumulating evidence indicates that memory T cells developed during past bacterial and viral infection can cross-react with unrelated pathogens, including transplant antigens, and can alter responses to de novo infections, vaccines, cancers, or rejection. Therefore, careful examination of T cell responses elicited by CMV is warranted to understand their potentially beneficial or harmful roles in future major immune events. Our detailed exploration of the distribution, phenotype, TCR repertoire and transcriptome of CD4+ T cells within CMV seropositive healthy individuals using high-dimensional flow cytometry and single cell multi-omics sequencing reveals that CMV seropositivity has highly significant age-independent effects, leading to a reduction in CD4+ naïve T cells and an expansion of CD4+ effector memory T cells and CD45RA+ effector memory T cells. These induced CD4+ effector memory T cells undergo a specific differentiation trajectory resulting in a subpopulation of CD57+CD27-CD28-CD244+ CD4+ T cells with cytotoxic function and TCR oligoclonality for optimal controlled coexistence with cytomegalovirus. Through gene set enrichment analysis, we found that this subpopulation is similar to virus-specific CD8+ T cells and T cells that mediate acute rejection in patients using tacrolimus and belatacept, a selective costimulation blocker. Together, these data suggest that memory CD4+ T cells induced by cytomegalovirus are formed via a distinct differentiation program to acquire cytotoxic function and can be potentially detrimental to transplant patients adopting costimulation blockade immunosuppressive regimen.